A Quadcopter at Your Service-108 with Secure Delivery of Medicine - Gokula, G; Minavathi, Minavathi (International Journal of Computer Sciences and Engineering, 2023)
Revolutionizing supply chain dynamics, medicine-carrying drones facilitate a stable vertical flight for seamless supply transfers to remote areas. Empowered by Ardupilot, an open-source Unmanned Vehicle Autopilot software suite, these drones showcase advanced flight control capabilities. GPS ensures precise navigation, while Mission Planner, intricately connected with MAVLink, optimizes quadcopter operations. The RFID-Arduino Nano interface secures the container housing medical resources. Post-compilation, the code dynamically runs, extracting RFID card serial numbers for heightened security. Exclusive access is granted solely to cards with designated UIDs, fortifying overall mission security and reliability. This abstract encapsulates a technological nexus, converging advanced flight systems and robust security measures, propelling medicine delivery to new frontiers with efficiency and precision.